Effect of Oven-Drying and Lyophilization on Proximate Composition, Ascorbic Acid Content and Screening of Phytochemical Components in Garcinia xanthochymus Hook.f. and Garcinia morella (Gaertn.Desr) Available in Bodoland Territorial Region (BTR) of Assam, India - Brahma, J.; Ray, S.; Islary, A. (Journal of Scientific Research, 2025)
The present study aimed to focus on the influence of successive oven drying and lyophilization on proximate composition, ascorbic acid content, and phytochemical screening of Garcinia xanthochymus (GX) and Garcinia morella (GM). GX extract exhibited high levels of crude fiber (11.45 %), high moisture content (13.92 %), and ash content (3.77 %) compared to GM (crude fiber: 10.25 %, moisture content: 11.45 % and total ash content: 2.78 %). Conversely, GM had higher fat (0.45 %) and crude protein (4.5 %) contents compared to GX (fat: 0.14 %; protein: 4.04 %). Carbohydrates were the most abundant with GX containing 78.13 % and GM 72.23 %. GX also exhibited a higher level of reducing sugars (12.39 %) and ascorbic acid (78.59 mg/100 g) compared to GM (carbohydrate: 3.8 % and ascorbic acid: 72.32 mg/100 g). The variability in nutritional composition was influenced according to species, collection location, and sample source. GC-MS was employed to evaluate phytochemical constituents where GM showed a maximum (30 numbers) in comparison to GX (9 numbers) in terms of alkanes, phenols, fatty acids, terpenes, and steroids.